1993
DOI: 10.1139/m93-026
|View full text |Cite
|
Sign up to set email alerts
|

Indoleacetic acid production by the rhizosphere bacterium Azospirillum brasilense Cd under in vitro conditions

Abstract: Factors influencing indoleacetic acid release from Azospirillum brasilense Cd (ATCC 29729) were investigated under batch culture conditions. In the presence of ammonium in the liquid culture solution, indoleacetic acid release from bacterial cells was considerably higher than in the corresponding N-free medium that was slightly solidified with agar to provide conditions for N2 fixation. In the solution culture, the concentration of indoleacetic acid was low during the logarithmic growth phase and increased rap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0
3

Year Published

2005
2005
2018
2018

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(22 citation statements)
references
References 16 publications
1
18
0
3
Order By: Relevance
“…No significant differences in pH were found between cultures supplemented with IAA and those supplemented with PAA, indicating that the slightly higher expression of the ipdC gene in the presence of PAA can be intrinsically attributed to PAA itself and is not due to a pH effect. (30,41,10,58,43,57). Secondary metabolism is often brought on by exhaustion of a nutrient (suboptimal growth conditions), biosynthesis or addition of an inducer, or a growth rate decrease (16).…”
Section: Resultsmentioning
confidence: 99%
“…No significant differences in pH were found between cultures supplemented with IAA and those supplemented with PAA, indicating that the slightly higher expression of the ipdC gene in the presence of PAA can be intrinsically attributed to PAA itself and is not due to a pH effect. (30,41,10,58,43,57). Secondary metabolism is often brought on by exhaustion of a nutrient (suboptimal growth conditions), biosynthesis or addition of an inducer, or a growth rate decrease (16).…”
Section: Resultsmentioning
confidence: 99%
“…These rhizobacteria, like those introduced in the present experiment are associated with the roots of the grass, due to the influence of organic compounds product of root exudates, such as carbohydrates, organic acids and microbial growth factors (Omay et al, 1993;Chelius and Triplett, 2000). However, by not using specific laboratory techniques in this field, the authors of this paper cannot issue a conclusion with respect to defining this outcome, nor to those shown in Table 3, which suggest the marked influence of native microorganisms in some variables.…”
Section: Experiments With Triticummentioning
confidence: 77%
“…Estas rizobacterias, al igual que las introducidas en el presente experimento, se asocian a las raíces de la gramínea, debido a la influencia de compuestos orgánicos producto de los exudados radicales, como: carbohidratos, ácidos orgánicos y factores de crecimiento microbiano (Omay et al, 1993;Chelius y Triplett, 2000). No obstante, al no utilizar las técnicas de laboratorio específicas en este campo, los autores del presente trabajo no pueden emitir una conclusión definitoria con respecto a este resultado, ni a los mostrados en el Cuadro 3, los cuales sugieren la influencia marcada de los microorganismos autóctonos en algunas variables evaluadas.…”
Section: Experiments With Zea Maysunclassified
“…Tryptophan on rhizosphere could be obtained from the degradation of root cell and microbial cell and root exudates. This showed that IAA was produced during the late exponential and stationer phases (Omay et al, 1993). Spaepen et al (2007) mentioned that the role of IAA to the bacteria has not clearly known yet.…”
Section: Effect Of Incubation Time On the Production Of Indole-3-acetmentioning
confidence: 95%